Design of a Compact UWB MIMO Antenna without Decoupling Structure - Yanjie Wu; Kang Ding; Bing Zhang; Jianfeng Li; Duolong Wu; Kun Wang (International Journal of Antennas and Propagation)
A compact high isolation ultrawideband (UWB) multiple-input-multiple-output (MIMO) antenna is designed. The proposed MIMO antenna consists of a rectangular monopole antenna and a slot antenna fed by two microstrip lines, respectively. To improve the impedance matching, a circular coupling structure is designed to feed the tapered slot antenna. The parasitic resonance introduced by the ground stub helps to extend the impedance bandwidth of monopole antenna at the upper UWB band. Commonly used complex decoupling or coupling structures are eliminated that endow the proposed antenna minimized foot print, which is preferred in mobile handset. Although without decoupling structure, high isolation is obtained between two antenna elements. Simulation and measurement verify the antenna’s desirable performance, showing a broad impedance bandwidth of 3.1–10.6 GHz with |S11| < −10 dB and |S21| < −20 dB over 3.4–10.6 GHz, and |S21| < −18 dB from 3.1–3.4 GHz.